Triangle A B C has area equal to 4 9 0 3 and perimeter equal to 3 0 . Also, one of its angles is equal to 6 0 ∘ . What is the product of the sides of A B C ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think that is cos 60° instead of sin 60°. The sides are 12, 7.5, 19.5.
x , y , z are sides of △ A B C Suppose : angle ( x , y ) = 6 0 ∘ .
so S = 2 1 x y sin 6 0 ∘ = 4 9 0 3 , hence x y = 9 0 .
By cosine formula,
z
2
=
x
2
+
y
2
−
2
x
y
c
o
s
6
0
.
->
(
3
0
−
x
−
y
)
2
=
x
2
+
y
2
−
9
0
(cause
x
+
y
+
z
=
3
0
,
x
y
=
9
0
)
->
9
0
0
−
6
0
(
x
+
y
)
+
2
x
y
=
−
9
0
->
x
+
y
=
3
9
/
2
(cause
x
y
=
9
0
)
->
z
=
2
1
/
2
->
x
y
z
=
9
0
×
2
1
/
2
=
9
4
5
[Latex edits]
We can assume that triangle ABC has AB = c, BC = a, CA = b and \angle BAC = 60 ^ \circ. [ABC] = \frac {1}{2}bc\sin \angle BAC = \frac {90\sqrt{2}}{4} Therefore bc = 90.
Then we apply the law of cosine: a^2 = b^2 + c^2 - 2bc\cos\angle BAC = b^2 + c^2 - 90 a^2 + a^2 = a^2 + b^2 + c^2 - 90 2a^2 + 90 = a^2 + b^2 + c^2
We also have a + b + c = 30 Then (a + b + c)^2 = 900 Or a^2 + b^2 + c^2 + 2ab + 2bc + 2ca = 900 Because a^2 + b^2 + c^2 = 2a^2 + 90 and bc = 90 Then a^2 + ab + ac = 315 Or a(a+b+c) = a*30 = 315 This leads to a = 21/2.
Because bc = 90, a = 21/2, then abc = 945.
Given a triangle with sides a , b , c and α - the angle between a and b , we know that the area A = 2 a b sin α and that c 2 = a 2 + b 2 − 2 a b cos α (the later is known as the law of cosines). It is given that 2 a b sin α = 4 9 0 3 , also a + b + c = 3 0 and α = 6 0 ∘ . It is well known that sin 6 0 ∘ = 2 3 and cos 6 0 ∘ = 2 1 . From the area we get a b = 9 0 . From the law of cosines, c 2 = a 2 + b 2 − a b . From the perimeter, c 2 = ( 3 0 − a − b ) 2 = 9 0 0 − 6 0 ( a + b ) + a 2 + b 2 + 2 a b . After putting the last two equations together, the squares cancel out and all that remains is 6 0 ( a + b ) = 9 0 0 + 3 a b = 1 1 7 0 ⟹ a + b = 2 3 9 . Finally from perimeter, c = 3 0 − ( a + b ) = 2 2 1 and a b c = 9 0 ⋅ 2 2 1 = 9 4 5 .
[Note - Given a + b = 2 3 9 , a b = 9 0 how would you solve for a and b ? - Calvin]
All other solutions were marked wrong. This ranged from
Using the wrong formulas.
Claiming that a 'magical formula' exists, and somehow concluding that c = 1 0 . 5 .
Refusing to use punctuation which made equations not make sense. If the equation reads x = 2 y = 3 z = 4 x , my conclusion is that x = y = z = 0 . If you expect me to magically insert commas for you, then I'd do that everywhere, and a b c = 9 0 ( 1 0 . 5 ) = 9 4 5 will become a , b c = 9 0 , ( 1 0 . 5 ) = 9 4 5 .
Having numerous computation errors in the proof, even one claiming that 9 0 × 2 1 9 = 5 8 5 as the answer.
Recognize a random scalene triangle can be broken into two right triangles by drawing the altitude from any given vertex. Given that one angle is 6 0 ∘ we have one 30-60-90 triangle and the key to the problem.
Let the sides of our 30-60-90 triangle be a , 2 a , and 3 a respectively (the altitude is 3 a ). Concerning the side of our scalene with length a let the remainder be b . According to the Pythagorean theorem, the remaining side of the scalene has length b 2 + 3 a 2 . We can now describe the perimeter and area of our scalene triangle in terms of a and b ; with two unknowns and two equations we can now solve.
For the Area:
Area 4 9 0 3 2 9 0 3 2 9 0 4 5 b = 2 1 a ∗ 3 a + 2 1 b ∗ 3 a = 2 1 a ⋅ 3 a + 2 1 b ⋅ 3 a = a ∗ 3 a + b ⋅ 3 a = a ⋅ a + b ⋅ a = a 2 + a b = a 4 5 − a 2
For the Perimeter: Perimeter 3 0 3 0 − 3 a − b ( 3 0 − 3 a − b ) 2 9 0 0 − 1 8 0 a − 6 0 b + 9 a 2 + 6 a b + b 2 9 0 0 − 6 0 b + 6 a b = 2 a + a + b + b 2 + 3 a 2 = 3 a + b + b 2 + 3 a 2 = b 2 + 3 a 2 = b 2 + 3 a 2 = b 2 + 3 a 2 = − 6 a 2 + 1 8 0 a
Substituting in the above: 9 0 0 − 6 0 ( a 4 5 − a 2 ) + 6 a ( a 4 5 − a 2 ) 9 0 0 − a 2 7 0 0 + 6 0 a + 2 7 0 − 6 a 2 1 1 7 0 1 1 7 0 a 0 0 = − 6 a 2 + 1 8 0 a = − 6 a 2 + 1 8 0 a = 1 2 0 a + a 2 7 0 0 = 1 2 0 a 2 + 2 7 0 0 = 4 a 2 − 3 9 a + 9 0 = ( 2 a − 7 . 5 ) ( 2 a − 1 2 )
Potential solutions: a = 6 , 7 . 5
Plugging a = 6 into b = a 4 5 − a 2 we get b = 1 . 5 . Which we plug into our perimeter equation 2 a + a + b + b 2 + 3 a 2 to verify is 30.
Checking the other solution a = 7 . 5 , b becomes negative.
We have but to solve the original question, what is the product of the lengths of the three sides:
The first side is a + b = 6 + 1 . 5 = 7 . 5 .
The second side is 2 a = 2 ⋅ 6 = 1 2 .
The third side is b 2 + 3 a 2 = 1 . 5 2 + 3 ⋅ 6 2 = 1 0 . 5
So the solution is 7 . 5 ⋅ 1 2 ⋅ 1 0 . 5 = 9 4 5
Q.E.D.
WLOG, let two sides that make up the 60 degree angle be be $BC=a$ and $AC=b$. Then by the given, $\frac{1}{2}ab\sin C=\frac{1}{2}ab\sin 60^\circ=\frac{90\sqrt{3}}{4}$ so $ab=90$ and thus $b=90/a$.
Now using the Law of Cosines, we find that the remaining side has length $$\sqrt{a^2+8100/a^2-90}.$$ However, the perimeter is 30 so it can also be expressed as $$30-a-90/a.$$ Setting these expression equal, we find that $$a={15/2, 12}$$ which are $a$ and $b$. Then $c=\frac{21}{2}$ so the product of the side lengths is $$12\left(\frac{15}{2}\right)\left(\frac{21}{2}\right)=945.$$
Let AB=c,BC=a and CA=b $$[ABC]=90\sqrt{3}/4$$ or, $$\frac {1}{2} \times AB \times AC \times \sqrt{3}/2=90\sqrt{3}/4$$ $$\Rightarrow b \times c=90$$ Again $$[ABC]=\sqrt {s} \times \sqrt {s-a} \times \sqrt {s-b} \times \sqrt {s-c}$$ where s=semiperimeter=15 $$\Rightarrow 15(15-a)(15-b)(15-c)=24300$$ $$(15-a)[225-15(b+c)+90]=\frac {1620}{16}$$ $$(15-a)[315-15(30-a)]=\frac {1620}{16}$$ Hence we get,$$4a^{2}-96a+567=0$$ Solving the eq. we get $$a=\frac {108}{8},\frac {84}{8}$$ $$\Rightarrow a \times b \times c=945$$
First, since one of the angles in this triangle is 60° (let’s call this angle C) we know that sin C = √3/2 and cos C= 1/2 .
The problems states that Area = (90√3)/4. Using the equation that Area = ½ ab sinC (where sides a and b are adjacent to angle A) ½ ab √3/2 = (90√3)/4 so the product ab = 90
Using a manipulation of the cosine rule, we know that cosC=(a^2+b^2-c^2)/( 2ab). Substituting in cos C= 1/2, and ab=90, we get that: 1/2=(a^2+b^2-c^2)/( 2(90)) or that 90 = a^2+b^2-c^2.
Using 90=a^2+b^2-c^2 and completing the square we obtain: 90=(a+b)^2-2ab-c^2 Since the perimeter is 30,we know a + b + c = 30, or a + b = 30 – c. Using this eqation with ab = 90, and substituting we find that:
90=(30-c)^2-2(90)-c^2
90=900-60c+c^2-180-c^2
90=900-60c-180
90=720-60c
So, c = 11.25.
Therefore abc = 90 × 11.25 = 945.
using hero's formula ; s(s-a)(s-b)(s-c)= A*A s = (a+b+c)/2=15 area= ab sin 60/2 -- ab=90; replace c as 30-(a+b); solve for a+b.. we get a+b = 39/2 -- c = 21/2-- abc = 945
Let AC be b,AB be c and bC be a Assuming ABC is 60 degree. Area of triangle =0.5acsin60 ac=90 The are many possible values of a and c, below are some of them 4 and 22.5 5 and 18 6 and 15 9 and 10 12 and 7.5 Using cosine rule,b^2=c^2+a^2-2accos60 We found that the values of a and c is 12 and 7.5. Hence b is 30-12-7.5= 10.5 Product of the sides of ABC =abc=12x7.5x10.5=945
let,angle B=60, a,b,c be the arms of the triangle ABC perimeter=a+b+c=30; area=0.5 a c sin(B); by writing the value of area,we get a c=90; we also know,area=under root(s(s-a)(s-b)(s-c)),where s=(a+b+c)/2 by solving,we get b=(21/2) or (27/2) but, if b=(27/2), a b c>999 so,according to the given condition, a b c=945. when b=(21/2)(i.e ans<999)
Without loss of generality, let ∠ B A C = 6 0 ∘ . Let [ A B C ] denote the area of triangle A B C and let C B = a , A C = b and A B = c .
Thus [ A B C ] = 2 1 b c sin 6 0 ∘ = 4 3 b c = 4 9 0 3 ⇒ b c = 9 0 , and a + b + c = 3 0 . From the law of cosines we have a 2 = b 2 + c 2 − b c = ( b + c ) 2 − 3 b c .
Substituting b c = 9 0 and b + c = 3 0 − a into the last equation gives a 2 = ( 3 0 − a ) 2 − 3 × 9 0 ⇒ a = 2 2 1 . Thus b + c = 2 3 9 .
Substituting b = 2 3 9 − c into b c = 9 0 , we get ( 2 c − 1 5 ) ( c − 1 2 ) = 0 which gives b = 2 1 5 , c = 1 2 or b = 1 2 , c = 2 1 5 .
Hence a b c = 2 2 1 × 2 1 5 × 1 2 = 9 4 5 .
Two step solution is: Use formula for area of triangle 2 1 a c s i n ( 6 0 ) , and the other one is the half angle formulae which says that t a n ( 6 0 / 2 ) = s ( s − b ) A r e a o f t r i a n g l e where s is semi-perimeter. And I think this also avoids the possibility of other solution.
Let the angle 60^\circ is between side a and b. Area of triangle ABC is 4 9 0 3 = 2 1 a b sin 6 0 ∘ = 4 a b 3 ⇒ a b = 9 0 . Applying Heron's formula, we have s ( s − a ) ( s − b ) ( s − c ) = 4 9 0 3 = 1 6 2 4 3 0 0 ⇒ s ( s − a ) ( s − b ) ( s − c ) = 1 6 2 4 3 0 0 , where s is half of the perimeter, which is equal to 15. a,b and c are the length of sides of the triangle. So, 1 6 2 4 3 0 0 = 5 0 6 2 5 − 1 5 a b c + 2 2 5 ( a b + b c + c a ) − 3 3 7 5 ( a + b + c ) = 5 0 6 2 5 − 1 5 ( 9 0 ) c + 2 2 5 [ 9 0 + c ( 3 0 − c ) ] − 3 3 7 5 ( 3 0 ) = − 2 2 5 c 2 + 5 4 0 0 c − 3 0 3 7 5 . Applying quadratic formula on 1 2 c 2 − 2 8 8 c + 1 7 0 1 = 0 , we have c = 1 0 . 5 or c = 1 3 . 5 . So, there are actually 2 answer, which are a b c = 9 0 ⋅ 1 3 . 5 = 1 2 1 5 or a b c = 9 0 ⋅ 1 0 . 5 = 9 4 5 .
Let the side lengths of the triangle be a,b, and c, and the angle of 60 be between sides a and b. Notice that by the Sine Area Formula, we have:
1/2 (a)(b)sin(60) = 90sqrt(3)/4 ab = 90
Also, by the Law of Cosines, we have:
c^2 = a^2 + b^2 - 2ab cos(60) = a^2 + b^2 - ab = (a+b)^2 - 3ab
We now make the substitution x = a+b. Thus, c = 30 - (a + b) = 30 - k. We substitute this into the above equation from the Law of Cosines:
(30 - k)^2 = k^2 -3(90) k^2 - 60k + 900 = k^2 - 270 k = 1170/60 = 39/2
Thus, c = 21/2, so the answer is abc = (90)(21/2) = 945.
(Note: The Preview did not render my LaTeX properly, so I didn't bother TeXing it.)
by using various formulas of trignometry we can find.
area=90.root3 /4=45.root3 /2. 1/2 product of two sides sine of angle between them=area of a triangle. by this,product of two sides=90. by using another area fomula,we can find that the third side is 10.5. thus product=90*10.5=945.
the triangle has sides a, b and c, one of its angles is 60, I will assume angle BCA = 60 (angle C) since everything is unknown it is possible.
perimeter formula : a+b+c= 30............... 1
cos rule : c^2= a^2+b^2-2ab cos 60...............2
area formula : 1/2 ab sin 60= 90√3/4.........................3
From 1,
c= 30-a-b
c^2= 900-60(a+b)+(a+b)^2
c^2= 900-60(a+b) + a^2+2ab+b^2
From 3,
ab = 90
Subs 3 to 1,
c^2= a^2 +b^2 - 60(a+b) +900 + 2x90
= a^2 +b^2 - 60(a+b) +1080
subs 3 to 2,
c^2= a^2 + b^2 -90
compare equation for c^2,
a^2 + b^2 - 90 = a^2 +b^2 - 60(a+b) +1080
-90 = - 60(a+b) +1080
-60(a+b)= -1170
a+b= 19.5.................4
Subs 4 to 1
19.5+c=30
c=10.5
abc =90x 10.5
=945
Let ∠ C = 6 0 ∘ .
[ABC] = 2 1 a b ∗ sin ∠ C = 4 9 0 3 . Then, ab = 90.
By the Law of Cosines, c 2 = a 2 + b 2 − 2 a b cos ∠ C . Noting that c = 3 0 − a − b , then substituting for ab and cos ∠ C , we get ( 3 0 − a − b ) 2 = a 2 + b 2 − 9 0 , which expands and simplifies to give 4 9 5 + a b = 3 0 ( a + b ) .
Since ab = 90 and a + b = 30 - c, we rearrange to get 3 0 c = 3 1 5 , or c = 19.5. The desired answer equals abc, which is 9 0 ∗ 1 9 . 5 = 5 8 5 .
Problem Loading...
Note Loading...
Set Loading...
Let x and y be the sides adjacent to the 6 0 ∘ angle, and z the opposite side. First we have Area = 2 1 x ⋅ y ⋅ s i n 6 0 ∘ ⇒ 4 9 0 3 = 2 x ⋅ y 2 3 ⇒ x ⋅ y = 9 0 .
Now, by the law of cosines we have: z 2 = x 2 + y 2 − 2 ⋅ x ⋅ y ⋅ c o s 6 0 ∘ ⇒ z 2 = x 2 + y 2 − x ⋅ y .
We also have x + y + z = 3 0 ⇒ z 2 = ( 3 0 − x − y ) 2 ⇒ z 2 = 9 0 0 + x 2 + y 2 − 6 0 ⋅ x − 6 0 ⋅ y + 2 ⋅ x ⋅ y .
Using all three equations we arrive at x + y = 2 3 9 ⇒ z = 2 2 1 ⇒ x ⋅ y ⋅ z = 9 0 ⋅ 2 2 1 = 9 4 5 ■